Membangun Wilayah Perbatasan di Provinsi Kepulauan Riau (Mencari Solusi Untuk Peningkatan Kesejahteraan Masyarakat Di Pulau-Pulau Terdepan) - Agus Hendrayady (Kemudi, 2019)
In the Riau Islands Province which is a problem in the border region, among others, is the very wide stretch of border areas, still lack of management of potential and natural resources both state and private, handling border areas that have not been maximized and are still partial or sectoral, education and welfare levels which is still low compared to people in neighboring countries such as Singapore and Malaysia, the lack of security and defense facilities and infrastructure which can lead to weak supervision of violations of state borders, and the lack of integration of programs and activities in border area development.The formulation of the problem in this study is: How are the efforts to Build a Border Area in the Riau Islands Province in order to find a solution to improve community welfare on the front islands. The aim of the study was to find out how the government's efforts in Building Border Areas in the Riau Islands Province in order to improve Community Welfare on the Leading Islands. This study uses library research methods, namely by using secondary data from sources that are used as objects of research, both books or literature, electronic media (internet sites), online media, which have to do with the problem of this research. Data collection in this study was conducted using library studies. The efforts made by the Riau Islands Provincial Government to find solutions to improve the welfare of the people on the leading islands are the Launching of the Integrated Border Area Movement Development Program (Gerbangdutas) in Natuna Regency, Accelerating rehabilitation of habitable homes, markets, schools, health centers, Village and Village Development Acceleration Program (P3DK), efforts to resolve national borders, and increase electrification, especially in small islands and remote areas through the construction of solar power plants, micro hydro power plants and power plant technology development Electric Power and construction of ports / piers in the border area. On the other hand, because of the strategic nature of the Riau Islands Province, it needs to be supported by good connectivity, especially sea connectivity. Therefore, a number of ports and ferry boats are built which are a priority so as to reduce intra-regional and inter-regional disparities. Batam as a city that also borders directly with neighboring Singapore is used as an industrial, tourism, shipping and service area. Another form carried out in the context of building border areas is by implementing the Sea Toll Program. It is expected that with the relationship between sea ports, there will be smooth delivery of goods to border areas. The Sea Toll Program is carried out, especially for the Riau Islands Province because the Riau Islands region has many seas. Whereas in the field of infrastructure, especially related to infrastructure, the Provincial Government of Riau Islands and PT. PLN in Riau Region and Riau Islands faces many obstacles, especially for border areas with many disruptions and constraints, especially because the condition of the Riau Islands is the sea, in addition to weather and climate factors which are often uncertain and the absence of port loading and unloading facilities.